The Rise of Islamic Environmentalism: Bibliometric Mapping of Green Islam Research - Judijanto, Loso; Nurhaliza, Ellys (West Science Islamic Studies, 2025)
This study analyzes the intellectual development and worldwide context of Islamic environmentalism, also referred to as Green Islam, via a bibliometric mapping of works indexed in Scopus from 1990 to 2025. The analysis employs VOSviewer and the Bibliometrix R-package to identify prominent authors, institutions, nations, and theme clusters influencing the discourse on Islam and environmental sustainability. The findings indicate that the domain has evolved from initial religious and philosophical discourse to interdisciplinary interactions encompassing Islamic law, ethics, finance, and education. Southeast Asia, especially Indonesia and Malaysia, stands out as the principal center of academic output and collaboration, with fundamental values like stewardship (khalīfah), balance (mīzān), and trust (amānah) forming the foundation of intellectual advancement. Notwithstanding its expansion, the discipline continues to be inadequately represented in empirical environmental research, indicating a necessity for enhanced interdisciplinary integration. This study enhances the theoretical framework of Islamic eco-ethics and provides practical guidance for policymakers and faith-based groups aiming to integrate Islamic principles with sustainability initiatives.